King Richard III - Shakespeare, William, 1564-1616. ([Auckland, N.Z.] : Floating Press, 2008)
Richard III belongs to Shakespeare's folio of King Richard plays, and is the longest of his plays after Hamlet. It is classified variously as a tragedy and a history, showing the reign of Richard III in an unflattering light. The play's length springs in part from its reference to the other Richard plays, with which Shakespeare assumed his audience would be familiar. These references and characters are often edited out to create an abridged version when the play is performed for modern audiences.
ACT IVScene I. London. Before the Tower; Scene II. London. A Room of State in the Palace; Scene III. London. Another Room in the Palace; Scene IV. London. Before the Palace; Scene V.A Room in Lord Stanley's House; ACT V; Scene I. Salisbury. An Open Place; Scene II. Plain Near Tamworth; Scene III. Bosworth Field; Scene IV. Another Part of the Field; Scene V. Another Part of the Field.
eBooks on EBSCOhost
Keywords: Richard -- III, -- King of England, -- 1452-1485 -- Drama; Richard -- III, -- King of England, -- 1452-1485; Great Britain -- History -- Richard III, 1483-1485 -- Drama; Great Britain; English; Languages & Literatures; English Literature; 1483-1485; History; Drama; Historical drama